Distribution and Implementation of Foot Mouth Disease Policy in the East Java Region - Novarina Sulsia Ista'In Ningtyas drh. M.Si (Universitas Pendidikan Mandalika, 2026)
Livestock in Indonesia is an important sector as one of the economic supports in improving the welfare of farmers. The resurgence of Foot and Mouth Disease (FMD) in Indonesia is a major problem that has a major impact on the economic sector. The high rate of spread and mortality prompted the government to take quick steps to tackle the FMD outbreak. One of the affected areas and is an area densely populated with livestock is in East Java. This study uses a quantitative descriptive design with a Geographic Information System (GIS) approach that describes the distribution of FMD in the East Java region in the first quarter of January-May 2025. The data taken is data on the number of cases that occurred in several regions in East Java. The sample of this study uses the reporting of the number of livestock suffering from FMD which is then presented in the form of maps and narratives. Based on the results, the areas that have a high incidence rate of disease are Pacitan, Ponorogo, Nganjuk, Kediri, Jombang and Lamongan. One of the government's efforts is to limit livestock traffic, improve biosecurity and biosevety and establish an FMD handling task force team.